Upaya Media Massa Online dalam Menghadapi Berita Hoax (Jurnal Kajian Media, 2018)
Initially there were only two types of media, namely printed media and broadcast media. As time goes by, online media appear. Information is getting easier and faster. Society does not only get information, but can also become as a source of information. However, we do not know whether the news has been verified correctly or not. The rise of hoax becomes one of the problems in communication. This study aims to determine the role of online mass media in facing hoax. Three most frequently accessed online mass media in Indonesia are selected in this research, namely Tribunnews.com, Detik.com, and Kompas.com. The theory used is Social Responsibility Theory. The method used in this research is qualitative descriptive with primary data collection techniques obtained through semi-structured interview, and secondary data through books, journals, and internet. This research found that in facing hoax, media journalists do verification by visiting the crime scene, making a call to authorities. The presence of media is to provide the correct, credible information, verify incoming information and to enlight the minds of the reader. Detik.com and Kompas.com have an anti-hoax feature on their news portal where people can make reports on news that they suspect as a hoax.Keywords:Role of Online Mass Media, Hoax, Social Responsibility Theory, Nine Elements of Journalism, Verification.